Removal of nickel (Ni2+) metal ion from its aqueous solution by iron oxide and kaolin clay minerals: A kinetic and equilibrium study - Sen, Tushar (Institution of Engineers (India), 2010)
In this work, the effect of various experimental parameters on kinetics and equilibrium adsorption of nickel Ni(II) metal ion from its aqueous solution by iron oxide and kaolin have been investigated using batch adsorption experiment. It has been found that the amount of adsorption of nickel metal ion increases with initial metal ion concentration, contact time, solution pH but decreases with increase in adsorbent concentration. The kinetic adsorption experimental results have been analysed using pseudo-first-order, pseudo-second-order kinetic model and intra-particle diffusion model respectively. It has been found that the adsorption kinetics was fitted pseudo-second-order kinetic model among other models. The kinetic parameters including rate constants at different initial metal ion concentrations, pH and at different adsorbent doses have also been estimated. The Langmuir and Freundlich adsorption isotherm models are used to describe the experimental data and Langmuir model has better linear correlation coefficient than other model. The value of separation factor, RL from Langmuir isotherm equation and rate of adsorption, 'n' from Freundlich model also gives an indication of favourable adsorption.